Assessment of Dental Materials’ Catalogs Based on Safety and Protection Items in Dental School of Kerman - shojaeepoor, Saeedeh; bahramnejad, Zahra; Torabi Parizi , Molook; Shojaeipour, Raziyeh; Hashemi nejad, Jelveh; Moslemi, Fatemeh; Dabiri , Donya (Journal of Dental School, 2021)
Objectives Dental materials are potentially hazardous and can negatively affect the health of patients, dental staff, and the surrounding environment. Thus, it is important to be aware and comply with the information provided in the material safety data sheets (MSDSs). Therefore, it seems necessary to review the dental material safety sheets in order to determine their consistency with the standard safety items required for dental materials. This study aimed to evaluate the MSDSs of dental materials consumed in Kerman Dental School to determine their compliance with the standard safety items. Methods In this cross-sectional study, 106 dental materials were selected from 12 clinical departments of Kerman Dental School. The MSDSs were assessed in order to determine their consistency with the standard safety items. Data were analyzed with SPSS version 21, and t-test was used for statistical analysis. Statistical significance level was set at P<0.05. Results Among the 15 items considered necessary according to the standard MSDSs, the item “necessary measures in case of possible leakage and spillage” had been least frequently stated in the assessed MSDSs. Also, the mean safety score of the materials with MSDSs was significantly higher compared with materials that had no MSDSs(P=0.0001). Conclusion Evaluation of the MSDSs of dental materials consumed in Kerman Dental School regarding the required standard items revealed that they did not meet the defined standard levels.